Optimalisasi Alat Muat Dan Alat Angkut Dengan Menggunakan Metode Quality Control Circle Untuk Memenuhi Target Produksi Tambang Bijih Emas Bawah Tanah Di PT. Dempo Maju Cemerlang, Kabupaten Pesisir Selatan, Provinsi Sumatera Barat. - ilham siddiq; Mulya Gusman (Departemen Teknik Pertambangan FT UNP, 2021)
Based on ore production data at PT. Dempo Maju Cemerlang found that the production target is 1500 tons / month, while what it gets is 900 tons / month. The contributing factors are the inadequate work of the loading equipment, transportation equipment, and the presence of a time slot. Ideal conditions in the production process are very difficult to achieve, this can be pursued by optimizing these tools. One of the methods used is the quality control circle (qcc) method. The actual production of loading equipment is 1298,21 tonnes / month and transportation equipment is 1414,09 tonnes / month. Identification of problems seen from human, machine, and environmental factors. The actual production is 1200 tons, and the actual productivity of the loading equipment is 1298.21 tons / month and the transportation equipment is 1414.09 tons / month. while the target of ore production is 2100 tons / month. After optimization, it was found that the ore production was 2111 tons, and the productivity of loading equipment was 2297.87 tons / month and transportation equipment was 2513.90 tons / month. So, the optimization obtained is 49.17% for loading equipment and 50.50% for conveyances of the required target, around 40.56% increase in loading tool productivity and 34.04% increase in conveyance productivity. It can be concluded that the increase in production carried out by the qcc method has been achieved. So it requires equipment maintenance management, rail checking, and increased operator discipline.